Wandering stars: About planets and exo-planets; An introductory notebook - Cole, George H. A. (London, Imperial College Press, 2006)
The space vehicle spectaculars of recent years have been revealing the full scope and beauty of our own solar system but have also shown that a growing number of other stars too have planetary bodies orbiting around them. It seems that our galaxy contains untold numbers of planets, and presumably other galaxies are similar to our own.
Glossary 435-473p.; Index 485-488p.
Keywords: Astronomy; Planets; Star; Mathematics